Commentary: The Drury Report and Political Development in the N.W.T. - Dickerson, Mark O. (ARCTIC, 1982)
The author's commentary on the Drury Report provides an interesting insight into the relationship of the people of the north and the federal government, as well as providing a useful critique on many aspects of the Report itself.